2018
DOI: 10.1097/txd.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Rabbit Antithymocyte Globulin Induction Dosing for Kidney Transplantation

Abstract: BackgroundRabbit antithymocyte globulin (rATG) is the most widely used kidney transplant induction immunotherapy in the United States. It was recently Food and Drug Administration approved for this indication with typical dose recommendations of 1.5 mg/kg for up to 7 days given via a central line.MethodsWe theorized that reduced rATG dosing when compared with conventional dosing (6-10.5 mg/kg) is safe and effective, leading to development of a risk-stratified treatment protocol. Five-year data from a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Several studies have demonstrated excellent 1-year graft outcomes with low-dose rATG induction strategies. In a comparison to conventional rATG exposure targets of 6–10 mg/kg, Singh et al 6 reviewed their outcomes using a tailored rATG cumulative exposure target of 3–6 mg/kg over a 5-year period and found comparable outcomes to those reported in the Scientific Registry of Transplant Recipients. Another study by Grafals et al 12 utilizing a much lower rATG cumulative exposure target of either 2.25 or 3.75 mg/kg demonstrated a biopsy-proven acute rejection rate of 10% and 17%, respectively, at 1-year follow-up and similar T-cell subpopulation depletion and repopulation kinetics in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated excellent 1-year graft outcomes with low-dose rATG induction strategies. In a comparison to conventional rATG exposure targets of 6–10 mg/kg, Singh et al 6 reviewed their outcomes using a tailored rATG cumulative exposure target of 3–6 mg/kg over a 5-year period and found comparable outcomes to those reported in the Scientific Registry of Transplant Recipients. Another study by Grafals et al 12 utilizing a much lower rATG cumulative exposure target of either 2.25 or 3.75 mg/kg demonstrated a biopsy-proven acute rejection rate of 10% and 17%, respectively, at 1-year follow-up and similar T-cell subpopulation depletion and repopulation kinetics in both groups.…”
Section: Discussionmentioning
confidence: 99%
“… 4 However, the lack of specific dosing recommendations until very recently has led to many immunosuppressive protocols in the adult transplant literature with an overall trend toward a lower cumulative exposure in the most recent era. 6 , 10 12 By utilizing the NAPRTCS registry, a large voluntary database that collects information on pediatric kidney transplants performed across North America, 8 we provide a contemporary assessment of the prevailing practice patterns at 37 participating centers with regards to rATG use for induction therapy. We demonstrate a wide variability in rATG cumulative exposure between individual centers, yet an overall trend toward lower exposure in the most recent era.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When CD8 + T cells undergo homeostatic proliferation they take on the phenotype of memory T cells (socalled pseudo-memory T cells) without ever having been exposed to antigen, including a decreased dependence on IL-2 and costimulation through CD28. 25 They also elegantly show that B cells are necessary to the process of homeostatic proliferation, but not through antigen presentation, since MHC knock out on B cells has no effect T-cell repopulation, but global MHC-I KO completely prevents T-cell expansion. 25 They also elegantly show that B cells are necessary to the process of homeostatic proliferation, but not through antigen presentation, since MHC knock out on B cells has no effect T-cell repopulation, but global MHC-I KO completely prevents T-cell expansion.…”
Section: Homeostatic Proliferation Following Lymphodepletionmentioning
confidence: 99%
“…26 promotes the memory phenotype of expanding T cells during homeostatic proliferation, but blocking the IL-27 receptor prevents the expansion of any T cells after depletion in mouse models. 25 They also elegantly show that B cells are necessary to the process of homeostatic proliferation, but not through antigen presentation, since MHC knock out on B cells has no effect T-cell repopulation, but global MHC-I KO completely prevents T-cell expansion. Finally, they go on to show that the cytokine production by B cells is the critical component to CD8 T-cell reconstitution following depletion by mATG.…”
Section: Homeostatic Proliferation Following Lymphodepletionmentioning
confidence: 99%